Longitudinal Study of the Association Between Screen Time and Childhood Obesity in Singapore - Eng, Robert; Badrool Nizham (Phlox Institute: Indonesian Medical Research Organization, 2024)
Introduction: Childhood obesity is a growing public health concern in Singapore. Excessive screen time has been identified as a potential risk factor for childhood obesity. This longitudinal study aims to investigate the association between screen time and the development of childhood obesity in a Singaporean cohort. Methods: A prospective cohort study was conducted involving 500 children aged 6-12 years in Singapore. Screen time data was collected through questionnaires at baseline, 1 year, and 3 years. Anthropometric measurements were taken at the same time points to assess body mass index (BMI) and obesity status. Multivariate regression analysis was used to examine the association between screen time and obesity, adjusting for potential confounders. Results: Increased screen time was significantly associated with an increased risk of developing obesity. Each additional hour of screen time per day at baseline was associated with a 1.2-fold increased risk of obesity at 3-year follow-up (OR: 1.2, 95% CI: 1.05-1.37). The association remained significant after adjusting for age, gender, socioeconomic status, physical activity, and dietary habits. Conclusion: This study provides evidence for a longitudinal association between screen time and childhood obesity in Singapore. Interventions targeting screen time reduction should be considered as part of a comprehensive strategy to prevent childhood obesity in Singapore.